West to east dispersal and subsequent rapid diversification of the mega-diverse genus Begonia (Begoniaceae) in the Malesian archipelago (2011)
Aim The complex palaeogeography of the Malesian archipelago, characterized by the evolution of an ever?changing mosaic of terrestrial and marine areas throughout the Cenozoic, provides the geographic backdrop for the remarkable diversification of Malesian Begonia (>?450 species). This study aimed to investigate the origin of Malesian Begonia , the directionality of dispersal events within the Malesian archipelago and the impact of ancient water gaps on colonization patterns, and to identify drivers of diversification. Location Asia, Southeast Asia, Malesia. Methods Plastid DNA sequence data of representatives of all families of the Cucurbitales and Fagales (mat K, rbc L, trn L intron, trn L–F spacer, 4076 aligned positions, 92 taxa) and a sample of all major Asian Begonia sections (ndh A intron, ndh F–rpl 32 spacer, rpl 32–trn L spacer, 4059 aligned positions, 112 taxa) were analysed under an uncorrelated?rates relaxed molecular clock model to estimate the age of the Begonia crown group divergence and divergence ages within Asian Begonia . Ancestral areas were reconstructed using a likelihood approach implementing a dispersal–extinction–cladogenesis model, and with a Bayesian approach to dispersal–vicariance analysis. Results The results indicated an initial diversification of Asian Begonia in continental Asia in the Miocene, and subsequent colonization of Malesia by multiple lineages. There was support for at least six independent dispersal events from continental Asia and western Malesia to Wallacea dating from the late Miocene to the Pleistocene. Begonia section Petermannia (>?270 species) originated in Western Malesia, and subsequently dispersed to Wallacea, New Guinea and the Philippines. Lineages within this section diversified rapidly since the Pliocene, coinciding with rapid orogenesis on Sulawesi and New Guinea. Main conclusions The predominant trend of Begonia dispersals between continental Asia and Malesia, and also within Malesia, has been from west to east. The water bodies separating the Sunda Shelf region from Wallacea have been porous barriers to dispersal in Begonia following the emergence of substantial land in eastern Malesia from the late Miocene onwards. We hypothesize two major drivers of the diversification of Malesian Begonia : (1) the formation of topographical heterogeneity and the promotion of microallopatry by orogenesis in the Pliocene and Pleistocene; and (2) cyclic vicariance by frequent habitat fragmentations and amalgamations due to climate and sea?level fluctuations during the Pleistocene.